Towards a history of the Basque language - Hualde, José Ignacio, 1958-; Lakarra, Joseba; Trask, R. L. (Robert Lawrence), 1944-2004 (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 1995)
Questions related to the origin and history of the Basque language spark considerable interest, since it is the only surviving pre-Indo-European language in western Europe. However, until now, there was no readily available source in English providing answers to these questions or giving an overview of past and current research in this area. This book is intended to partly fill this void. The book contains both state-of-the-art papers which summarize our knowledge about particular areas of Basque historical linguistics, and articles presenting new hypotheses and points of view based on hard evi.